EVALUATION OF PROSTATE BASAL CELL BY CYTOKERATIN 903 STAINING IN PROSTATIC ADENOCARCINOMA GLEASON SCORE 6 - Nasution, Ramlan; Sugandi, Suwandi; Sihombing, Aaron Tigor; Yantisetiasti, Anglita; Hernowo, Betthy S (Indonesian Urological Association, 2010)
Objective: To evaluate the role of prostate basal cell staining in diagnosing Gleason score 6 prostate cancer. Materials & Methods: During research period, we collected 20 medical records and paraffin block specimens of Gleason score 6 prostatic adenocarcinoma patients. Specimens were taken from prostate needle biopsy. Demographic data and PSA level were extracted from medical records. Basal cells were detected by immunohistochemical staining for antikeratin 34β-E12 on paraffin block specimens analyzed by an experienced pathologist. Positive results suggest a benign lesion. Results: Mean age is 70 ± 6,5 years. Mean prostate volume and PSA level was 52±17cc and 25±21 ng/ml. Three specimens (15%) showed presence of basal cells on antikeratin 34β-E12 staining, which indicated benign lesions. Leucocyturia was found in all patients of this group. There was a significant association between PSA level and antikeratin 34β-E12 staining (p=0,03). In multivariate analysis, there is no significant association between antikeratin 34β-E12 staining with age, prostate volume, and leucocyturia. Conclusions: 15 % cases of prostatic cancer Gleason score 6 still showed basal cell existence. Immunohistochemical staining of basal cell should be considered in suspicious cases of prostatic cancer.